RELATIONSHIP BETWEEN TNF-238G>A POLYMORPHISM AND PREDISPOSITION TO PULMONARY TUBERCULOIS INFECTION IN THE INDONESIAN POPULATION (A PILOT STUDY) - Putri, Syurlia; Rasmiyyah, Sausan; Huskany, Evita Amalia; Razari, Intan; Wicaksono, Britanto Dani; Yuliwulandari, Rika (Lembaga Penelitian Universitas YARSI, 2015)
Previous studies suggested that genetic factors exerted huge influence in susceptibility to Tuberculosis. Tumor Necrosis Factor Alpha (TNF-a), which is encoded by the TNF gene, play a role on pulmonary macrophage function in isolating and controlling Mycobacterium tuberculosis infection. Polymorphisms on the promoter region of the TNF gene have been predicted to affect its transcriptional activity. Therefore, these polymorphisms are an excellent candidate to further study the role of TNF-a in susceptibility to Tuberculosis. 100 pulmonary tuberculosis patients (case) and 100 healthy individuals (controls) were recruited for this pilot study. DNA samples from cases and controls were genotyped for the TNF -238G A SNP (rs361525) using LightSNip genotyping assay. Our results showed no significant difference in the distribution of TNF -238 genotypes in case and control subjects (P = 0.4335). Further investigation on TNF -238 allele frequencies between case and control studies also yields no significant difference (P=1.000; OR=1.000; %95CI [0.246597 ? 4.055200]) which may suggest that there are no association with predisposition to Tuberculosis infection. In conclusion, this pilot study showed that the TNF -238G A SNP is not associated with susceptibility to Tuberculosis.